Histogram-Based Reversible Data Hiding with Quadtree Concepts - Huang, Hsiang-Cheh; Wang, Ting-Hsuan; Fang, Wai-Chi (Security Technology, Disaster Recovery and Business Continuity, 2010)
Reversible data hiding has attracted much attention in researches during the past few years. With its characteristics of reversibility, the algorithm is required to fulfill the goals that at the encoder, the secret information needs to be embedded into the original image by some means, and at the decoder, both the secret information and the original image are required to be correctly extracted and recovered, and they should be identical to their embedding counterparts. Under the requirement of reversibility, for evaluating the performance of the algorithm, the output image quality, called imperceptibility, and the number of bits for embedding, called capacity, are the two important factors to access the effectiveness of the algorithm. Here we take the concepts of quadtree decomposition into consideration to watch the characteristics of the original content. And we propose a reversible data hiding algorithm that has the ability to reside more capacity than conventional algorithm, with similar output image quality after embedding, and comparable side information produced.